Electrocatalytic hydrogen production on a modified pencil graphite electrode - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
The development of Polyaniline (PAni)-Chitosan (Chi) and PAni-Chi/Au conducting composite films coated on pencil graphite and used as electrocatalysts for hydrogen production from water is discussed in this study for the first time. The obtained PAni-Chi composite films and PAni-Chi/Au nanostructured composite films were characterized by scanning electron microscopy (SEM), energy-dispersive spectrometer (EDS) and evaluated as hydrogen evolution reaction (HER) electrocatalysts in an acidic medium. The effect of the film thickness of the PAni-Chi composite film and the effect of the Au electrodeposition on this film were systematically studied by cyclic voltammetry (CV), Tafel polarization curves and electrochemical impedance spectroscopy (EIS). It has been established that the main pathway for the HER is via the Volmer Heyrovsky mechanism with the Volmer reaction being the rate-determining step. This highly active, stable and cost-effective modified pencil graphite electrode is a promising electrocatalyst for hydrogen production from water. (C) 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Electrocatalyst; Conducting composite; Pencil graphite; Au nanoparticles; Hydrogen evolution; EVOLUTION REACTION; GOLD NANOPARTICLES; CONDUCTING POLYMER; HIGH-PRESSURE; REDUCTION; DINITROGEN; PALLADIUM; CARRIER